Analisis Pengaruh Harga dan Brand Trust Terhadap Perilaku Peralihan Merk Lisptik Revlon Pada Mahasiswa - Annur Fitri Hayati; Ridha Saputri (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
The purpose of this study was to determine the effect of price and brand trust on the brand switching behavior of Revlon lipstick on students of the Faculty of Economics, Padang State University. This type of research is causative. The population in this study were students of the Faculty of Economics, Padang State University. The number of research samples based on William Cochran's formula was 100 people and selected using the Purposive Sampling technique. The data used is the type of primary data obtained through distributing questionnaires to students of the Faculty of Economics, Padang State University with predetermined criteria. The analytical method used is multiple regression analysis using SPSS 22. The results show that (1) Price has a significant effect on brand switching of Revlon lipsticks to other brands of lipstick, (2) Brand trust has no significant effect on brand switching of Revlon lipsticks to other brands of lipstick. , (3) price has a significant effect on brand switching of Revlon lipstick to another brand of lipstick, while brand trust has no significant effect on brand switching of Revlon lipstick to another brand of lipstick.